Budget-aware task scheduling technique for efficient management of cloud resources. (19th September 2019) - Alworafi, Mokhtar A.; Dhari, Atyaf; El-Booz, Sheren A.; Mallappa, Suresha
Cloud computing technology offers many services using pay as per use concept where the user gets to specify constraints such as the budget. Task scheduling algorithms are therefore the most preferred option under a budget constraint which is used to improve some of the metrics like makespan and cost. In this paper, we propose a budget-aware scheduling (BAS) model to schedule the tasks based on the budget constraint. At first, the VMs which meet the budget are labelled and the task priority is determined. Next, the task attributes are checked and assigned to the resources which meet the budget constraint to keep makespan as low as possible with minimal cost for resource usage. The experiments demonstrate that the proposed model outperforms other algorithms by reducing average of makespan, mean of average response time, and the cost of resources with an increase in resource utilisation and profit of provider.